EVALUATION OF FAMILIAL ORAL LICHEN PLANUS : PRESENTATION OF 3 FAMILIES (BioMedical Research in Medicine (BMR Medicine) (ISSN 2349-0756), 2024)
Lichen planus (LP) is a relatively common disorder of the stratified squamous epithelia, which is, in many ways, an enigma. Lichen planus is probably of multi-factorial origin, sometimes induced by drugs or dental materials, often idiopathic, and with an immune-pathogenesis involving T-cells in particular. The occurrence of OLP appears to be complex, with interactions between and among genetic, environmental, and even lifestyle factors. Familial occurrence of alo has always been a debated topic with a limited literature available to support the relevance. In this case report series a total of 112 OLP cases were examined, out of which 3 families with a total of 7 patients were found to be having the familial correlation. The main objective of this paper is to present a case report series of 7 patients based on their familial correlation.